Give It Another Shot: Startup Experience and the Mobilization of Human Resources in New Ventures - Vera Rocha; Dario Pozzoli (Institute of Labor Economics (IZA), 2021)
Human resources can provide a competitive advantage to firms, but we still know little about how newly-founded ventures start mobilizing these resources. Given the central role of entrepreneurs' background in designing the strategy of new firms, we investigate whether and how startup experience, namely past performance as entrepreneurs, influences employee mobilization strategies in new ventures. Integrating behavioral theories of the firm with regulatory focus theory, we postulate that serial entrepreneurs who failed in the past are more likely to be prevention oriented and change their employee mobilization strategies towards a more targeted hiring approach in subsequent ventures. Using Danish register data, we compare the employee sourcing practices of serial entrepreneurs with their former practices as novice entrepreneurs, as well as with a control group of first-time entrepreneurs who engage in serial venturing later on. We find that entrepreneurs who have already failed (i.e. discontinued a former business) select their employees from fewer sources in the labor market. Our tests lend support for learning as a key mechanism driving these differences. Alternative mechanisms such as selection effects, stigma of failure, and demand-side constraints are not empirically supported.
Keywords: J24; L26; C01; 330; failure; hiring; new ventures; startup experience; human capital